AFRO-CENTRISM: THE CHALLENGE OF SOCIAL DEVELOPMENT - Osei-Hwedie, Kwaku (Social Work/Maatskaplike Werk, 2007)
African nations seek to escape from poverty, disease, ignorance, inequality and lack of opportunity. Despite massive investments in socio-economic development, the masses in many African countries still remain ill-fed, ill-housed, under-educated and vulnerable to preventable diseases such as HIV/AIDS, and malaria. The continent is characterised by increasing economic deprivation, generalised misery, a high incidence of poverty, environmental destruction and diminishing food security. This is underscored by the fact that the number of people living in extreme poverty (on U$1 or less a day) rose from 217 million in 1990 to 290 million in 2000 (Economic Commission for Africa (ECA), 2005). Governments and other stakeholders are constantly searching for better and more effective ways to tackle these problems in order to improve the welfare of their people.